A Systematic Mapping of Serious Games for the Rehabilitation of Fine Motor Coordination - Pereira, Rafael A.; Luz, Vinicius S. Garcia da; Riemer, Yasmin; Matos, Simone N.; Lopes, Rui P. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2022)
Motor development is an important part of an individual's evolution and the Serious game creation is a useful tool when used in motor development. This article carried out a systematic mapping to identify an overview of games aimed at rehabilitating fine motor skills. The objective was to identify scientific literature that addresses activities that stimulate the player's motor coordination and verify which ones are specific for fine motor skills and their characteristics. It was concluded that the use of mobile devices is still little explored, but it is a potential tool for the development of solutions for the rehabilitation of fine motor skills because it includes technologies such as accelerometer, gyroscope, and touchscreen, which allow the assessment of balance, tremors, direction, and tilt of the device. In addition, the touchscreen allows movements such as tapping, dragging, and pinching. Another finding is the lack of motor assessment methodologies, artificial intelligence applications, and game frameworks for coordination rehabilitation development.